Asymmetric Cycloetherifications by Bifunctional Aminothiourea Catalysts: The Importance of Hydrogen Bonding - Fukata, Yukihiro; Miyaji, Ryota; Okamura, Takaaki; Asano, Keisuke; Matsubara, Seijiro (Synthesis, 2013)
Chiral oxacyclic frameworks are prevalent in many natural products and bioactive compounds. In addition, a number of them are important synthetic intermediates. Thus, the synthesis of such structures is a significant goal in the field of organic chemistry. However, the development of catalytic asymmetric cycloetherification for the straightforward synthesis of these compounds remains a challenge. In this study, we propose the use of aminothiourea catalysis as an effective way to accomplish such a challenge. The asymmetric synthesis of chiral oxygen heterocycles, including tetrahydrofurans, tetrahydropyrans, and 1,3-dioxolanes, is demonstrated herein using intramolecular oxy-Michael addition mediated by bifunctional aminothiourea catalysts.
Keywords: oxycyclization; cycloetherification; hydrogen bonding; bifunctional aminothiourea catalyst; oxy-Michael addition